The Role of Corporate Social Responsibility in Enhancing Resilience and Sustainability of Manufacturing SMEs: A European Perspective - Windiana Wahyu Eka Putri; Wandira Regita Putri Cahyani (Pusat Riset dan Inovasi Nasional, 2024)
This study investigates the implementation of Corporate Social Responsibility (CSR) practices in the manufacturing sector, with a focus on comparing the experiences and outcomes of small and large enterprises in Europe. Utilizing a mixed-methods approach, the research examines how these enterprises adopt CSR practices and the resultant impacts on financial and environmental performance. The findings indicate that both small and large enterprises benefit significantly from CSR, evidenced by improvements in key financial metrics such as Return on Assets (ROA) and Return on Equity (ROE), as well as reductions in carbon emissions and enhancements in energy efficiency. Small enterprises, despite facing challenges such as limited financial resources and lack of expertise, achieve notable local community engagement and operational efficiencies through targeted CSR initiatives. Large enterprises leverage their extensive resources to implement comprehensive CSR strategies, resulting in substantial environmental and financial gains. The study highlights the importance of stakeholder engagement, government support, and a robust organizational culture in facilitating effective CSR adoption. These insights underscore the need for supportive measures to help SMEs overcome barriers and enhance their contributions to sustainable development.